Innovative technologies in the system of state and municipal management - E. N. Babina; O. A. Mukhoryanova; P. V. Shmygaleva (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the essential aspects of innovative personnel technologies in personnel management in modern conditions, the basics of the application of new personnel technologies in state and municipal government. The main trends in the development of personnel technologies are identified. The process of integrating artificial intelligence into HR technologies is highlighted. Information is provided on experiments aimed at introducing new methods of personnel work using information and communication technologies, as well as a remote form of civil servants performing professional service activities. The data of the analysis of the course of the digitalization process in the field of state and municipal government are reflected.